Experiences of gender-based violence in women asylum seekers from El Salvador, Honduras, and Guatemala: a retrospective, qualitative study. (March 2019) - Wang, Eileen; D'Andrea, Megan; Baranowski, Kimberly; Singer, Elizabeth
Abstract: Background: In 2016, around 65 000 women fled gender-based violence in the Northern Triangle (NTCA) countries of El Salvador, Honduras, and Guatemala, and attempted to seek asylum in the USA. Some women participate in medical evaluations by clinicians to document the effect of these human rights violations as part of the asylum process. The aim of this study is to elucidate the forms of persecution experienced by women in this region, and the physical and psychological sequelae of this violence. Methods: We undertook a retrospective, qualitative study of asylum-seeking adult women fleeing gender-based violence from the NTCA who were seen by evaluators in the Mount Sinai Human Rights Program from February, 2014, to August, 2018. We included any case in which the client self-identified as female, came from an NTCA country, and received a psychological evaluation. This study was approved by the Mount Sinai Institutional Review Board. We used a modified consensual qualitative research (CQR-M) approach to identify themes found across the archived and de-identified affidavits written as part of the medical evaluation. Findings: We included data from 70 women; mean age was 29·4 years (SD 6·5; range 18–55 years]. 24 women identified as Salvadoran, 15 as Guatemalan, and 31 as Honduran. All women reported violence perpetrated by their communities, families, intimate partners, and/or powerful gangs, and faced justice systems in their countries that they felt would not protect them. They had been subject to: verbal (50 women [71%]), physical (57 [81%]), and sexual (59 [84%]) assaults; death threats (58 [83%]); control (40 [57%]); extortion (24 [34%]); and harm, or threats of harm, to their children (50 [43%] and 22 [31%], respectively). Evaluators identified psychological symptoms associated with anxiety (56 women [80%]), depression (64 [91%]), and post-traumatic stress disorder (56 [80%]), as well as suicidality (33 [47%]). Women also reported physical injury including bruising, head injury and loss of consciousness, and gynaecological harm including miscarriage and forced sterilisation. Many women had been displaced within their own countries before fleeing and stated that they travelled with their children, experienced hazardous conditions and violence during their journey, and were detained on arrival in the USA. Finally, the women reported resilience associated with their religious beliefs, family, temperament, and ability to make meaning from their experiences. Interpretation: This study highlights the systemic nature of gender-based violence in the NTCA. The results also describe the perils that women from the NTCA encountered during their migration and demonstrate the continued structural violence that awaits them if they are denied asylum and returned to their countries of origin. Funding: None.